If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(-x+2)=-(3x-4)
We move all terms to the left:
5(-x+2)-(-(3x-4))=0
We add all the numbers together, and all the variables
5(-1x+2)-(-(3x-4))=0
We multiply parentheses
-5x-(-(3x-4))+10=0
We calculate terms in parentheses: -(-(3x-4)), so:We get rid of parentheses
-(3x-4)
We get rid of parentheses
-3x+4
Back to the equation:
-(-3x+4)
-5x+3x-4+10=0
We add all the numbers together, and all the variables
-2x+6=0
We move all terms containing x to the left, all other terms to the right
-2x=-6
x=-6/-2
x=+3
| 3x+5=(x+5)*2 | | 3r+6=-12 | | 2u+1=-17 | | 2-b+1=8 | | 4e+9=33 | | 2x/3-1/4-2=x | | 10x-3=5x+32 | | 6z+2=-10 | | 12x-7=2x+83 | | 12-4(3x-2)=42-15x | | 6z+2=-2 | | (43+b)/2=30 | | 12x^2-68x=-96 | | (43+b)/2=32 | | 4h+9=49 | | x3–x=30 | | 2l+2=0 | | .6x=800 | | 3a+8=9 | | (p+840)/8=535 | | 1-x=2x+2/3 | | 2x2+13x+7=0 | | 12w-45=4w+51 | | -12x^2-88x-20=0 | | k=-4,5 | | 6x+1=3(9x+1)+12 | | 0=-3x2+6x-8 | | 2²n+¹=512 | | 6x–9=3x+12 | | 7c-28=2c+22 | | 9g+7=4g-13 | | 2x+40=12x-120 |